Influence of Organizational Culture, Competence and Management Accounting Information System on Company Performance with Corporate Governance as Moderating Variables - Sari, Egi Gumala; Arsjah, Regina Jansen (International Journal of Business and Applied Economics, 2025)
This study aims to determine the influence of organizational cultural relationships, competencies and management accounting information systems on the performance of companies with corporate governance as moderating variables. The sample of 204 respondents divided into 4 Sharia financial institutions, namely Sharia banking, sharia multifinance, sharia insurance and Baitul Maal Wa Tamwil. This study found that corporate governance variables and management accounting information system variables have a positive and significant influence, while the other two variables namely organizational culture and competence have a positive but insignificant influence. The corporate governance as a moderating variable strengthens the relationship of organizational cultural variables and competencies although not significant. Corporate governance does not strengthen the relationship between management accounting information systems to the company's performance.